INVESTMENT OF CHARACTER VALUES CARE ENVIRONMENT IN LEARNING SCIENCE SOCIAL KNOWLEDGE BASED AUDIO VISUAL - Yonaka Adventa (Universitas Sebelas Maret, 2018)
Education is one important element in changing the life of society. Character education plays a role in shaping the personality of the younger generation. One of the values of character that is not less important to be cultivated to peseta students educate the environment. Through learning social science can include the values of character education by integrating the material in social science learning. Here learners love the environment more in a simple way like throwing garbage in place, taking care of plants, cleaning the environment. To support the learning of Social Sciences then a teacher uses the aid of audio visual learning media so that learners are able to understand the value of environmental care characters. This conceptual article as an insight in instilling the value of environmental caring character in Social Science learning through audio visual media.